ロケット ニヨル チキュウ ジバ カンソク - 遠山, 文雄; トオヤマ, フミオ; 青山, 巌; アオヤマ, イワオ; 加藤, 愛雄; カトウ, ヨシオ; TOHYAMA, Fumio; AOYAMA, Iwao; KATO, Yoshio (国立極地研究所, 1975)
P(論文) オーロラ・エレクトロジェット電流を間接的に測定するため,地球磁場の高度変化の観測を行った。その結果,ロケット上昇時と下降時に観測された磁場分布の顕著な差異から,オーロラ・ジェット電流の幅がかなりせまく,局在していることが結論できた. The S-210JA-7 sounding rocket was launched from Syowa Station, Antarctica to measure the magnetic field of the electrojet current at 0023 local time on December 14, 1972. Preliminary results show that there were remarkable differences between the upward and the downward profiles of the magnetic field. These profiles indicate that the current system of the electrojet is quite narrow and localized. departmental bulletin paper